READING OF IDEOLOGY BEHIND THE TEXT - Jama, Karolus Budiman (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
The city of Malang has long become a tourism destination and a center of education. Because of this, it impacted to the increasing of multiculture, multiethnic and varieties of faith within this city. In one side, the coming of some people from different background bring different value that can profitable of economic aspect in relation to tourism and studying about the diversity as a center of education. In the other side, that diversity can be a threat toward the existence of some people who have different faith and ideology. This writing is a critical reflection toward the text of “menerima kosan putri muslimah, dan putra muslim di Kota Malang” this text analysis is not based on research method but it is pure text analysis based on deconstruction theory as tool of analyzing the text in finding ideology.